1994
DOI: 10.1097/00006123-199405000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Anatomy of the Lower Cervical Spine and Cord

Abstract: The authors dissected the cervical spine and its surrounding structures from 40 adult cadavers under a surgical microscope. The anterior part of the spine and spinal cord was examined after vertebrectomy. The posterior longitudinal ligament (PLL) consists of two layers; the anterior one is termed the deep layer, and the posterior one is termed the superficial layer. These two layers adhered together loosely. In the lateral portion of the spinal canal, the superficial layer joined the periradicular sheath at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…[61516] Kirazli et al . found that the average number of dorsal thoracic rootlets is 6.6 ± 0.8, which is higher than what Sindou found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[61516] Kirazli et al . found that the average number of dorsal thoracic rootlets is 6.6 ± 0.8, which is higher than what Sindou found.…”
Section: Resultsmentioning
confidence: 99%
“…found an average of 6.8 T1 segment rootlets in their study which corresponded with the results of three other separate studies. [15181920] In addition, they found that T1 segment contained the largest number of thoracic nerve rootlets, in contrast to the T6, T7, and T10 segments which contained the fewest. [19] Kirazli et al .…”
Section: Resultsmentioning
confidence: 99%
“…Distal to the origin it ascended slightly medially in the spinal canal, dorsal to the deep layer of the posterior longitudinal ligament (PLL), and the ventral surface of the anterior internal vertebral venous plexus 12 (figure 1B-E). Rostrally, it gradual tapered, and penetrated the tectorial membrane, the upper extent of the PLL, just above the upper margin of the horizontal part of the cruciform ligament (figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The periradicular foraminal space is small and contains some fibrotic tissue. In particular, the superficial layer of the posterior longitudinal ligament is connected to the periradicular sheath anchoring the pedicle (17). When the needle tip is located in the small periradicular foraminal space, the contrast could initially collect on one side of the periradicular space without spreading to the other side around the nerve root.…”
Section: Discussionmentioning
confidence: 99%